Mechanisms of metabolic reprogramming in abdominal aortic aneurysm - Wu, Xiaodong; Li, Jianpeng; Ju, Qiaoyue; Zeng, Yuqi; Cao, Junjie (Frontiers in Cell and Developmental Biology, 2025)
Abdominal aortic aneurysm (AAA) is often asymptomatic in its early stages, and rupture poses a life threatening risk. Currently, no effective pharmacological therapies are available, underscoring the importance of mechanistic research. Metabolic reprogramming—an adaptive process encompassing glucose, lipid, and amino acid metabolism—has increasingly gained attention in the context of AAA. These metabolic shifts, which coordinate cellular energy supply, biosynthesis, and signaling, critically shape vascular smooth muscle cell (VSMC) behavior, macrophage polarization, extracellular matrix remodeling, oxidative stress responses, and immune activation. Importantly, growing evidence suggests that crosstalk among these metabolic pathways orchestrates complex pathophysiological networks driving AAA initiation and progression. Exploring AAA pathogenesis from an integrated metabolic perspective not only helps elucidate underlying mechanisms but also provides new insights and potential therapeutic targets.